Structural Deformation Analysis Design using Terrestrial Data - Batyr, Yusupov (IRC, 2019)
Deformation monitoring in Malaysia has become more important nowadays due to the increasing risk of hazardous tragedies such as landslide, subsidence and structural movement in engineering structures. Deformation can be defined as changes in the size or form of an object due to an applied load or external factors such as temperature, wind or change in ground water level.